Meningkatkan Kemandirian Anak Usia 5-6 Tahun Melalui Metode Bermain Peran - Nurhani Nurhani; Riskal Fitri; Ashar Ashar (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
Independence is a fundamental developmental aspect that must be instilled from an early age; however, in reality, many children aged 5–6 years at TK Bukit Permai 2 Karampang Eja still demonstrate low levels of autonomy and high dependence on adults. This study aims to improve the independence of children aged 5–6 years through the implementation of structured, child-centered role-playing methods. This type of research is a collaborative Classroom Action Research (CAR) adopting the Kemmis and McTaggart spiral model. The research subjects consisted of 15 children in Group B at TK Bukit Permai 2 Karampang Eja, Gowa Regency. The study was conducted in two action cycles, with each cycle encompassing the stages of planning, implementation, observation, and reflection. Data were collected through structured observation techniques using independence development assessment rubric instruments (covering indicators of physical ability, self-confidence, and responsibility) and reinforced by field notes and documentation. Data analysis techniques utilized descriptive percentage statistics for quantitative data and the Miles and Huberman interactive model for qualitative data. The results showed a highly significant escalation in the development of children's independence in each cycle. The average classical independence achievement of the children in the Pre-cycle condition was only 20.00%, which then increased to 42.22% at the end of Cycle I, and reached an optimal success rate of 82.22% at the end of Cycle II. This final figure successfully exceeded the predetermined action success indicator of 75%. The conclusion of this study proves that the role-playing method is empirically highly effective in holistically boosting early childhood independence.